RECURRENT AMELOBLASTOMA IN TEMPORAL REGION: A Case Recurrent Ameloblastoma - Mehmood, Maj Saad; Bukhari, Syed Gulzar Ali (Pakistan Armed Forces Medical Journal, 2010)
Ameloblastoma is a tumour of odontogenic epithelial origin and is composed of ameloblast like cells1. It is a benign locally invasive tumour with tendency to infiltrate beyond observed radiographic and clinical margins2. The clinical behavior may be regarded as lying somewhere between benign and malignant, and the high recurrence rate is a problem for clinicians 3.